Tackling Sclerotinia – an insight into the factors influencing disease development - Bennett, Sarita; Derbyshire, Mark; Michael, Pippa; Denton-Giles, Matthew; Lui, king yin; Thomson, linda (2019)
Key messages • Preconditioning temperatures between 35 and 50°C for 30 to 60 days increases sclerotia germination to 80%, compared to with no preconditioning • Sclerotinia stem rot infections were low in field trials in 2018, with a maximum 15% recorded, despite spores being present on 75 to 100% of petals tested • Sclerotia development is primarily below the point of infection in canola stems, with more and larger sclerotia recorded, below the point of infection. Greater overall sclerotia weight was recorded in the lower half of the lesion Aims 1. To determine the preconditioning temperatures required over summer and the winter temperatures required to initiate germination of sclerotia once wet 2. To record genotype by environment by management interactions that influence sclerotinia infections in the field, including prior soil assessment, petal testing and final disease score 3. To understand the relationship between stem lesion and sclerotia development in hybrid and open-pollinated canola varieties compared to with no preconditioning  Sclerotinia stem rot infections were low in field trials in 2018, with a maximum 15% recorded, despite spores being present on 75 to 100% of petals tested  Sclerotia development is primarily below the point of infection in canola stems, with more and larger sclerotia recorded, below the point of infection. Greater overall sclerotia weight was recorded in the lower half of the lesion Aims 1. To determine the preconditioning temperatures required over summer and the winter temperatures required to initiate germination of sclerotia once wet 2. To record genotype by environment by management interactions that influence sclerotinia infections in the field, including prior soil assessment, petal testing and final disease score 3. To understand the relationship between stem lesion and sclerotia development in hybrid and open-pollinated canola varieties